A call to be whole : the fundamentals of health care reform - Sowada, Barbara J., 1947- (Praeger, 2003)
Americans have the wealthiest health care system in the world, yet the health status of Americans ranks in the lowest quartile among the worldʼs 25 industrialized nations and 45 million Americans are without health insurance. Todayʼs cost, quality, and access problems are inter-related and can be traced to taken-for-granted assumptions and health careʼs outmoded organizing concepts: reductionism and materialism. Greater fragmentation of care, an over-dependence on technology, inattention to social and environmental determinants of health, and serious economic and moral dilemmas are some of the results of the last 40 years of piecemeal political and economic reform. This book has three purposes. The first is to help the reader see healthcare as a complex system-a part in a larger whole-and to show how answers to the questions, What is health? What is care? Who is responsible? How much is enough? implicitly define the purpose, effectiveness, efficiency, and fairness of a health care system. The second is to show that todayʼs access, cost, and quality problems are interrelated, and arise from outmoded concepts, unquestioned assumptions, and a long trail of inconsistent and contradictory answers to the four questions. The third purpose is to acquaint readers with both the personal and societal challenges of finding coherent answers to the four questions raised above and to describe some of the budding experimental solutions that challenge traditional conventions and assumptions.